Qualitative analysis of anti-abortion discourse used in arguments for a 6-week abortion ban in South Carolina - Lambert, Victoria C.; Hackworth, Emily E.; Billings, Deborah L. (Frontiers in Global Women's Health, 2023)
Background: On June 24, 2022, The US Supreme Court overturned Roe v. Wade, leaving abortion legislation entirely up to states. However, anti-abortion activists and legislators have organized for decades to prevent abortion access through restrictive state-level legislation. In 2019, South Carolina legislators proposed a bill criminalizing abortion after 6 weeks gestation, before most people know they are pregnant. The current study examines the anti-abortion rhetoric used in legislative hearings for this extreme abortion restriction in South Carolina. We aim to deconstruct the strategies and tactics used to restrict abortion access, position these strategies within the context of a post-Roe world, and illuminate the consequences of restrictive legislation. Methods: We qualitatively analyzed anti-abortion discourse used during legislative hearings of SC House Bill 3020, The South Carolina Fetal Heartbeat Protection from Abortion Act. Data came from publicly available videos of legislative hearings between March-November 2019, during which members of the public and legislators testified for and against the abortion ban. Videos were transcribed, and then testimonies were thematically analyzed using a priori and emergent coding. Results: Testifiers (Anti-abortion proponents) defended the ban using scientific disinformation and by citing advances in science to re-define “life”. A central argument was that a fetal “heartbeat” (i.e., cardiac activity) detected at 6 weeks gestation indicates life. Anti-abortion proponents used this to support their argument that the 6-week ban would “save lives”. Other core strategies compared anti-abortion advocacy to civil rights legislation, vilified supporters and providers of abortion, and framed people who get abortions as victims. Personhood language was used across strategies and was particularly prominent in pseudo-scientific arguments. Discussion: Abortion restrictions are detrimental to the health and wellbeing of people with the potential to become pregnant and to those who are pregnant. Efforts to defeat abortion bans must be grounded in a critical and deep understanding of anti-abortion strategies and tactics. Our results expose how extreme, inaccurate, and dangerous anti-abortion strategies, particularly their discourse, are and can be useful in developing effective approaches to countering anti-abortion rhetoric.